Investigating the Effect of an Intervention based on the Leventhal\'s Self-Regulation Model on the Sexual Function and Sexual Satisfaction of Women with Diabetes: A Randomized Clinical Trial - leila ghorbani; Zainab Alimoradi; Sima Hashemipour; Nasim Bahrami (مراقبت پرستاری و مامایی ابن سینا)
Background and Objective: The decline in sexual function and satisfaction is a common complication of diabetes in women. The present study aimed to investigating the effect of an intervention based on the Leventhal self-regulation model on the sexual fuction and sexual satisfaction of women with diabetes. Materials and Methods: This randomized controlled clinical trial was conducted with the participation of 88 women with diabetes between March and September 2023, who were assigned to either a control group or an intervention group using a four-way random block method. In the tintervention group, the intervention based on the Leventhal model was implemented through three face-to-face sessions per week. Sexual function, sexual satisfaction, and illness perception were examined in both groups before the intervention, after, and one, two, and three months post-intervention. Results: The mean difference in sexual satisfaction scores (95% CI) between the intervention and control groups in the first, second, and third follow-ups was 8.47 (3.15; 13.80), 8.98 (3.20; 14.76), 9.59 (3.78; 15.41), respectively. The mean difference in sexual function scores in the intervention group compared to the control group during the first, second, and third follow-ups was 0.43 (-0.74; 1.57), 0.76 (0.49; 2.01), 0.82 (-0.65; 2.29), respectively. The mean difference in illness perception scores in the intervention group compared to the control group during the first, second, and third follow-ups was -7.87 (-10.91; -4.82), -11.11 (-14.0; -8.23), -9/96 (-13.64; -6.29), respectively. Conclusion: The implementation of the Leventhal model as a straightforward and patient-centered approach is a suitable method to increase sexual satisfaction and improve illness perception among women with diabetes.